2017
DOI: 10.1371/journal.pone.0165934
|View full text |Cite
|
Sign up to set email alerts
|

Why are some languages confused for others? Investigating data from the Great Language Game

Abstract: In this paper we explore the results of a large-scale online game called ‘the Great Language Game’, in which people listen to an audio speech sample and make a forced-choice guess about the identity of the language from 2 or more alternatives. The data include 15 million guesses from 400 audio recordings of 78 languages. We investigate which languages are confused for which in the game, and if this correlates with the similarities that linguists identify between languages. This includes shared lexical items, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Another line of experimental research investigates the iconic potential of vocalization. A number of studies [138][139][140][141][142] using the 'guessing game' paradigm (see above) or the 'foreign language' paradigm [143] have shown that vocalizations have the capacity to be iconic. Hence, the authors argue that the vocal system might have played a role in protolanguage (for a review, see [144]).…”
Section: (E) Experimental Research On Communicationmentioning
confidence: 99%
“…Another line of experimental research investigates the iconic potential of vocalization. A number of studies [138][139][140][141][142] using the 'guessing game' paradigm (see above) or the 'foreign language' paradigm [143] have shown that vocalizations have the capacity to be iconic. Hence, the authors argue that the vocal system might have played a role in protolanguage (for a review, see [144]).…”
Section: (E) Experimental Research On Communicationmentioning
confidence: 99%
“…For example, both similarity of phoneme inventories and lexical similarity were identified as factors predicting the perceptual confusability (and, by implication, similarity) of languages in the Great Language Game (Skirgård et al, 2017). These authors report confusion asymmetries within the set of Slavic languages, i.e., cases of speakers of one language (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Skirgard et al [3] said a language will be confused like greeting words when the language or greeting words is rarely heard by someone, therefore to avoid this, of course a breakthrough is needed by getting used to hearing language or greeting words in order to avoid this confusion becoming a habit. In another ways McCullough et al [4] there are two kind perception of regional dialect variation namely: (1) Adult perception, and (2) Children's perception who across the lifefan: identification and discrimination.…”
Section: Introductionmentioning
confidence: 99%